Application of Organonitrofos and Inorganic Fertilizer on Cassava (Manihot Esculenta Crantz) in Ultisol Soil - Dermiyati, .; Lumbanraja, Jamalam; Banuwa, Irwan Sukri; Triyono, Sugeng; Maulida, Oktarina; Agsari, Debby (JOURNAL OF TROPICAL SOILS, 2015)
A field experiment was conducted to find out a combination dose of a novel organic fertilizer (Organonitrophos, OP) and inorganic fertilizers (N, P, and K) for the growth and yield of cassava (Manihot esculenta Crantz) during two planting periods of 2012-2013 and 2013- 2014 in ultisol soil (low in nutrients and organic matter) of Bandarlampung. The treatments were a six combination of organic and inorganic fertilizer. The experiments were laid out in a randomized block design with three replications. The difference combination of Organonitrophos and NPK fertilizers showed significantly effects on the plant height, the NPK sorption of total plant and total root, and the yields of cassava. The highest NPK sorption of total plants and total yields and the highest yields of cassava were found in N45P36K120OP1,000 kg ha-1 combination for the two planting periods. Based on Relative Agronomic Effectiveness (RAE) of cassava root yield, it can be concluded that 45-36-120-1,000 N-P-K-Organonitrophos kg ha-1 was the best combination dose of inorganic and organic fertilizers for the production of cassava in ultisol soil of Bandarlampung. [How to Cite: Dermiyati, J Lumbanraja, IS  Banuwa,  S Triyono,  O  Maulida  and  D  Agsari. 2015. Application of Organonitrofos and Inorganic Fertilizer on Cassava (Manihot Esculenta Crantz) in Ultisol Soil. J Trop Soils 20: 167-172. Doi: 10.5400/jts.2015.20.3.167]